2020
DOI: 10.1186/s12913-020-4909-0
|View full text |Cite
|
Sign up to set email alerts
|

A developmental evaluation of an intraprofessional Pharmacy Communication Partnership (PROMPT) to improve transitions in care from hospital to community: A mixed-methods study

Abstract: Background: People transitioning from hospital-to community-based care are at increased risk of experiencing medication problems that can lead to adverse drug events and poor health outcomes. Community pharmacists provide medication expertise and support during care transitions yet are not routinely included in communications between hospitals and other primary health care providers. The PhaRmacy COMmunication ParTnership (PROMPT) intervention facilitates medication management by optimizing information sharing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
(35 reference statements)
1
10
0
2
Order By: Relevance
“…This was surprising, as doctors and nurses acknowledged and valued the role of pharmacists to manage medications at admission and discharge; yet, the processes for updating pharmacists about changing plans at these transition points were unreliable. Our findings support earlier work, which found that patients were sometimes transferred without pharmacists’ knowledge [ 12 ], and a lack of intraprofessional pharmacist handover between ward transfers was also seen in a study examining patient transfers between emergency departments and medical wards [ 19 ]. Another study similarly reported missed opportunities of interprofessional collaboration to enhance medication safety and frequent impromptu interactions [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was surprising, as doctors and nurses acknowledged and valued the role of pharmacists to manage medications at admission and discharge; yet, the processes for updating pharmacists about changing plans at these transition points were unreliable. Our findings support earlier work, which found that patients were sometimes transferred without pharmacists’ knowledge [ 12 ], and a lack of intraprofessional pharmacist handover between ward transfers was also seen in a study examining patient transfers between emergency departments and medical wards [ 19 ]. Another study similarly reported missed opportunities of interprofessional collaboration to enhance medication safety and frequent impromptu interactions [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recent research examining medication management across transitions of care has focused on medication incidents [ 3 , 8 ], pharmacist-led interventions [ 9 , 10 , 11 , 12 ] and patient and family perspectives [ 13 , 14 ]. Research also identifies communication breakdowns contributing to medication incidents across transitions [ 15 , 16 ]; yet, little is known about what influences how health professionals communicate with each other to manage medications and avoid potential breakdowns in communication across transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how the MARCH programme was delivered and determining critical moderating factors clarifies whether the non‐significant effect of the programme was due to poor implementation or due to ineffectiveness of the programme as such and is necessary to implement and improve transitional care programmes. Several complex pharmacy‐led transitional care studies have been conducted 13–16,26–31 . However, only a few have evaluated its implementation fidelity 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recognition of the corresponding pharmacist by the hospital could allow the pharmacist to send all correspondence such as hospital consultation letters or hospital discharge letters, as was already claimed [ 26 ]. Some countries such as Ohio (United States of America), Canada, and United Kingdom have already implemented programs to enhance the transition in care with positive results on patients [ 27 ] and less hospital readmissions, respectively [ 28 , 29 ]. For a few months in the United Kingdom, a program named Transfers of Care Around Medicines (TCAM) uses an online platform to transfer the discharge information to the community pharmacy chosen by the patient, which can contact him for a follow-up [ 30 ].…”
Section: Discussionmentioning
confidence: 99%